Detection QTLs for grain quality traits and yield in two BILs population of rice - Maryam Hosseini; Saadolah Houshmand; Shahram Mohamadi; Alireza Tarang; Mahmod Khodambashi; Hossein Rahimsouroush (Syiah Kuala University, 2011)
Abstract. Rice, the second most important crop after wheat, has been cultivated in Iran. Marketing conditions and quality traits after yield are the most important factors to adopt of new varieties. Therefore in recent years Iranian scientists decided to training on breeding improved high yield varieties with good grain quality.Quantitative trait loci (QTLs) yield and grain quality traits of rice (Oryza sativa L.) with additive, epistatic, and QTL × environment (QE) interaction effects were studied using a mixed-model-based composite interval mapping (MCIM) method and two populations of Back cross inbred lines (BILs) with a common maternal parent.In each of the populations two or three main effects of QTLs were detected for yield, amylose content, gel consistency and gelatinization temperature. Some identified QTL clusters suggested pleiotropic effects could control these traits. The phenotypic variation of AAE and AA QTLs effects were smaller than main QTLs. We conclude that the major genes and some minor and modifier genes controlled rice grain quality and yield components. The information obtained in this study have used to manipulating the QTLs for these traits by molecular marker-assisted selection and the best lines with excellent quality and high yield recognized